2013
DOI: 10.1049/iet-cta.2012.0897
|View full text |Cite
|
Sign up to set email alerts
|

H control of single‐machine infinite bus power systems with superconducting magnetic energy storage based on energy‐shaping and backstepping

Abstract: This article studies the H ∞ control problem for single-machine infinite bus power systems with superconducting magnetic energy storage (SMES) via simultaneous design of generator excitation control and SMES control. In the control system design, the exciter dynamics and unknown external disturbances are considered for practical implementation in power systems. A new synthesis framework is proposed to address the robust control problem of power systems with SMES. First, from the energy perspective, the interco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…The basic design of 10‐kJ class SMES can be found in , high‐filed HTS SMES coil , 200‐kJ 2G HTS solenoidal SMES coil can be found in , and their thermal and cooling design can be found in . The SMES founds application in mitigating the wind energy system fluctuations , voltage harmonics and enhancing stability , and its modern prospectus applications are given in . Robust controller schemes such as fuzzy logic, hysteresis, H‐infinity and sliding mode control schemes have been applied to SMES in conjunction with voltage source converter in MG .…”
Section: Other Applications and Future Prospectus Of Superconducting mentioning
confidence: 99%
“…The basic design of 10‐kJ class SMES can be found in , high‐filed HTS SMES coil , 200‐kJ 2G HTS solenoidal SMES coil can be found in , and their thermal and cooling design can be found in . The SMES founds application in mitigating the wind energy system fluctuations , voltage harmonics and enhancing stability , and its modern prospectus applications are given in . Robust controller schemes such as fuzzy logic, hysteresis, H‐infinity and sliding mode control schemes have been applied to SMES in conjunction with voltage source converter in MG .…”
Section: Other Applications and Future Prospectus Of Superconducting mentioning
confidence: 99%
“…In this paper, superconducting magnetic energy storage (SMES) devices, which have been considered to design power system stabilizers, are also investigated to solve the problem of LFC [17,18,19,20,21,22,23]. It was found that these SMES units using thyristor-converters and superconducting coil are able to compensate for the sudden large load disturbances, such as the start and/or stop of big industrial factories.…”
Section: Introductionmentioning
confidence: 99%
“…Unexpected system failures and external disturbances could also degrade the performance of a controller designed for a specific model. To overcome this problem, robust controllers are developed to deal with the uncertainties [25, 12–15]. The L 2 gain from the disturbance to the power system output can be maintained to a given level by the controllers designed in [4, 12].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this problem, robust controllers are developed to deal with the uncertainties [25, 12–15]. The L 2 gain from the disturbance to the power system output can be maintained to a given level by the controllers designed in [4, 12]. The H ∞ performance is achieved in [13] by solving a linear matrix inequality.…”
Section: Introductionmentioning
confidence: 99%